Exploration of Blockchain-Based Financial Models in Digital Asset Management: A Case Study in the Property and Real Estate Industry - PA Andiena Nindya Putri; Susanti Usman; Ng, Suwandi; I Ketut Kusuma Wijaya; Hedar Rusman (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This article presents a comprehensive literature review exploring the application of blockchain-based financial models in digital asset management, focusing on the property and real estate industry. Blockchain technology has garnered significant attention for its potential to revolutionize traditional financial systems by offering transparent, secure, and decentralized solutions. In the context of asset management, blockchain's immutable ledger and smart contract functionalities promise increased efficiency, reduced costs, and enhanced trust among stakeholders. Through a systematic review of existing literature, this study synthesizes key findings regarding the adoption, challenges, and opportunities of blockchain-based financial models in property and real estate asset management. The analysis encompasses aspects such as tokenization of assets, smart contracts for automated transactions, regulatory considerations, and industry-specific use cases. By examining current research and industry practices, this article contributes to a deeper understanding of how blockchain technology can reshape financial models and management strategies within the property and real estate sector.